2009
DOI: 10.2190/ec.41.1.b
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Improving Technology Integration Skills for Preservice Teachers Using the Teacher Work Sample

Abstract: This study explores the efforts at Brigham Young University to improve preservice candidates' technology integration using the Teacher Work Sample (TWS) as an assessment tool. Baseline data that was analyzed from 95 TWSs indicated that students were predominantly using technology for productivity and information presentation purposes even though they had been taught to use technology for active student learning. Researchers discovered that decisions made about technology integration were heavily influenced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
1
8
0
4
Order By: Relevance
“…If teachers are to engage in pedagogical innovation then they need to be prepared with knowledge beyond what is essential for operating in classrooms, as they are currently constituted (Law, ). However, research continues to find that, even in teacher preparation programmes that promote use of ICT for active student learning, ICT is used mostly for productivity and information presentation (Graham, Tripp, & Wentworth, ). Other research that directly addressed the question of innovation with pre‐service teachers found that their understandings of pedagogical innovation and capacity to deal with it varied (Davis, Hartshorne, & Ring, ) with the implication that programme designers need to consider readiness for change when promoting unfamiliar pedagogical approaches.…”
Section: From the Literaturementioning
confidence: 99%
“…If teachers are to engage in pedagogical innovation then they need to be prepared with knowledge beyond what is essential for operating in classrooms, as they are currently constituted (Law, ). However, research continues to find that, even in teacher preparation programmes that promote use of ICT for active student learning, ICT is used mostly for productivity and information presentation (Graham, Tripp, & Wentworth, ). Other research that directly addressed the question of innovation with pre‐service teachers found that their understandings of pedagogical innovation and capacity to deal with it varied (Davis, Hartshorne, & Ring, ) with the implication that programme designers need to consider readiness for change when promoting unfamiliar pedagogical approaches.…”
Section: From the Literaturementioning
confidence: 99%
“…Studies investigating interventions targeting TPACK or ICT skills have shown that these interventions can influence self-efficacy (Abbitt, 2011;Kiili et al, 2016;Torkzadeh & van Dyke, 2002), attitudes (Torkzadeh & van Dyke, 2002;Yerdelen-Damar et al, 2017), the use of technology (Graham et al, 2009;Keller et al, 2005) and TPACK (Abbitt, 2011;Cengiz, 2015). Regarding the potential to foster media-didactical competence and related constructs through trainings on digital media, we sought to investigate whether or not there are differences between trainers who attended a course on digital media and those who did not attend such a course.…”
Section: Group Differences In Attending a Course On Digital Mediamentioning
confidence: 99%
“…Enhanced and accessible text. When developing the GDWS, teacher candidates learn about technology through the experience (Chung, Davidson, & Yeh, 2011;Graham, Tripp, Wentworth, 2009;Hicks et al, 2007;Impedovo, Ritella, & Ligorio, 2013;Milman, 2005;Parker et al, 2012;Woodward & Nanlohy, 2004) and may become more confident using it (Boulton, 2014). In addition to Google Apps, teacher candidates learn how to create enhanced text using multimedia, embed academic supports through hyperlinks, and enable multimodal responses.…”
Section: Building the Gdws For Learning And Practicementioning
confidence: 99%